Presumptive Non-Ischemic Priapism in a Cat - Jeong-Min Lee; Ah-Won Sung; Han-Joon Lee; Joong-Hyun Song; Kun-Ho Song (Veterinary Sciences, 2022)
A 14-year-old neutered male British shorthair cat presented with a 21-day history of persistent erection and dysuria, along with overgrooming of the perineal region. Mild palpation induced pain and rigid corpora cavernosa with flaccid glans were observed during physical examination. Ultrasonography of the penis did not detect significant blood flow in the penile cavernosal artery. The drawing of aspirate blood from cavernosal bodies for gas analysis was impossible because of the anatomically small penis size of cats. Conservative management, including topical steroid ointment, lidocaine gel, gabapentin, and diazepam, was prescribed for supportive management. The clinical signs resolved, and ultrasonographic examination of the penis revealed no abnormalities. The cat remains clinically well without recurrence during the 6 months after treatment. To our knowledge, this is the first report of non-ischemic priapism in a cat.